Design and Analysis of Ultra Low-Profile ILA on a Rectangular Conducting Plane - Rohadi, Erfan; Firdaus Ali, Mochammad; Siradjuddin, Indrazno; Setiawan, Awan; Amalia, Amalia; Darmawan, Yudhi (International Journal of Engineering and Technology, 2018)
The unbalanced fed ultra low profile inverted L antenna on a rectangular conducting plane is proposed and analyzed numerically and experimentally.Â By adjusting the length and height of inverted L antenna, the feed point position, and the size of conducting plane, the return loss bandwidth and the directivity can be controlled. The return loss bandwidth of 2.57 % and the directivity of 4.34 dBi are obtained, when the size of conducting plane is 0.245 ï¬ (ï¬: wavelength) by 0.49 ï¬, and the antenna height is ï¬/30.Â The input impedance of the proposed antenna is compared with those of the conventional base-fed inverted L antenna and the base fed inverted F antenna.Â Although the directivity of base-fed inverted L antenna is almost same as that of proposed antenna, its input resistance becomes very low.Â In the base fed inverted F antenna, the return loss larger than 10 dB is not satisfied in the case of the antenna height less than 0.05 ï¬.Â Â Â